Clip thinking of generation Z: methods of developing students’ creative potential - Asiya R. Bukharbaeva; Lyudmila V. Sergeeva (RUDN Journal of Studies in Literature and Journalism, 2020)
The article is devoted to actual problem of clip thinking of generation Z. The goal of research is to determine the most effective methods of working with clip thinking taking into account the peculiarities of information perception by modern students. It covers phenomenon of clip thinking, its characteristics and origins. Positive and negative features of clip thinking are highlighted, as well as effective methods of university educational process applying having the trend of clip-based consumption of info by students. The authors conclude that clip thinking is a natural process: it is necessary to work competently with this phenomenon of generation Z. Its shown, that vast selection of digital tools is changing lifestyle of young generation, but multitasking, responsiveness, high degree of adaptability characterize modern students. The authors concluded that its necessary to form students' analytical and conceptual thinking in combination with clip thinking. Its not worth changing students or fight against clip thinking as well as to act according to old methodology of educational process. Modern students need in interesting cases of thinking efficiency, multitasking that requires active action. Specificity of case method application of teaching was substantiated empirically (including observation, experiment, survey), it develops creativity, increases the level of analytical and critical thinking, allows to work with a large amount of information, helps to study proposed business situations, analyzes data and make the respective decision. Its important to practice educational and search methods in a dialogue mode of learning process, construct situations, interactivity, mobility, frequent changes, multitasking. Clip thinking should be managed competently, by using its positive characteristics and preparing effective studying programs engaging relevant online and offline technologies.